Intuition in judgment and decision making - Plessner, Henning; Betsch, Cornelia; Betsch, Tilmann (Taylor and Francis, 2011)
First Published in 2008. Routledge is an imprint of Taylor & Francis, an informa company
Description based upon print version of record
Keywords: Electronic books